2016
DOI: 10.1038/cmi.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Innate recognition of Toxoplasma gondii in humans involves a mechanism distinct from that utilized by rodents

Abstract: Toxoplasma gondii is an intracellular protozoan parasite that infects rodents as part of its natural transmission cycle and induces disease in humans, an end-stage host. As one of the natural hosts of T. gondii, the mouse has been used extensively for elucidating the cellular and molecular basis of immunity to this pathogen while relatively few studies have focused on the response of humans. In our recent work, we identified CD16+ monocytes and DC1 dendritic cells as the major myeloid cell populations that res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
0
39
0
1
Order By: Relevance
“…28 In the present study, T. gondii induced a significant increase of TLR-9 protein expression, but did not affect TLR-2 or TLR-4 expression in HPCVE (Figure 1-2). 31 Another protozoan, Leishmania infantum, induces significant downregulation of TLR-4 and TLR-9 transcription in lymph nodes, but a significant upregulation of TLR-9 in skin from infected dogs. 29 However, it has been shown that TLR-9 is not required for the development of T. gondiiinduced ileitis in mice but that TLR-9 mediates distinct inflammatory changes in intestinal and extra-intestinal compartments including the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the present study, T. gondii induced a significant increase of TLR-9 protein expression, but did not affect TLR-2 or TLR-4 expression in HPCVE (Figure 1-2). 31 Another protozoan, Leishmania infantum, induces significant downregulation of TLR-4 and TLR-9 transcription in lymph nodes, but a significant upregulation of TLR-9 in skin from infected dogs. 29 However, it has been shown that TLR-9 is not required for the development of T. gondiiinduced ileitis in mice but that TLR-9 mediates distinct inflammatory changes in intestinal and extra-intestinal compartments including the brain.…”
Section: Discussionmentioning
confidence: 99%
“…30 Likely, is a more effective immune response against T. gondii in the digestive epithelia since it is the main infection route of this parasite in the intermediate hosts. 31 Another protozoan, Leishmania infantum, induces significant downregulation of TLR-4 and TLR-9 transcription in lymph nodes, but a significant upregulation of TLR-9 in skin from infected dogs. 32 Patients with Visceral Leishmaniasis, caused by Leishmania donovani, have high levels of expression of TLR-4 and TLR-9 in blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-established that T. gondii-mediated type I immunity requires DCs for host defense [25][26][27][28][29]. Work from our lab and others have demonstrated that DC-deficiency results in acute host susceptibility to T. gondii [26,30].…”
Section: T-bet Is Critical To Maintain Inflammatory Dcs During T Gonmentioning
confidence: 99%
“…Pioneering work identified the ability of macrophages to kill Toxoplasma (19,20), by employing both IFN-γ-dependent and -independent mechanisms to control intracellular parasite replication (21)(22)(23). While the mouse is a natural intermediate host and remains an important model to understand Toxoplasma pathogenesis, differences are emerging between the mouse and human in mechanisms of parasite control (5,(24)(25)(26)(27)(28). Therefore, to complement in vivo murine studies, a novel animal model can benefit analysis of Toxoplasma control on a cellular and molecular level.…”
Section: Introductionmentioning
confidence: 99%